If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 67 = 4(5 + 4b) + -1 67 = (5 * 4 + 4b * 4) + -1 67 = (20 + 16b) + -1 Reorder the terms: 67 = 20 + -1 + 16b Combine like terms: 20 + -1 = 19 67 = 19 + 16b Solving 67 = 19 + 16b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-16b' to each side of the equation. 67 + -16b = 19 + 16b + -16b Combine like terms: 16b + -16b = 0 67 + -16b = 19 + 0 67 + -16b = 19 Add '-67' to each side of the equation. 67 + -67 + -16b = 19 + -67 Combine like terms: 67 + -67 = 0 0 + -16b = 19 + -67 -16b = 19 + -67 Combine like terms: 19 + -67 = -48 -16b = -48 Divide each side by '-16'. b = 3 Simplifying b = 3
| x^(1/3)/x^(1/4)*x^(-3/4) | | -13=4n-3+n | | 72=3(-5n-1) | | 0.66666666666x-2=7 | | 2cos(2x-y)dx-cos(2x-y)dy=0 | | 9.8*7.9= | | 5x*(x+50)=29950 | | 21+7=31.64 | | 3p-7=-(p-4) | | 100=-4(6x-1) | | 5x-12=8-2x | | x^2-8+1=10 | | 3p+7=-(p-4) | | -90=5(2-5p) | | .05((1-x^6)/(1-x))=100 | | 24uv^4w^7-28u^4v^8=0 | | (1/6,-2) | | (3m+2n-7p)=-6m^3np^3-4m^2n^2p^3+14m^2np^4 | | 6x^3=729 | | 2(x+4)-2=4(x+2)-6 | | 50x^2-5x-3= | | 18x-3x=10 | | -10(s+1)=-71 | | 2/3a-4=4 | | 7c+2=5c-10 | | (x+2y)+(2x-3y)i+4i=5 | | (2x^2-3x+6)=-8x^3-24x^2 | | 3x=ax+1 | | (x+2)+(2x-3y)i+4i=5 | | 4/5f=2/3 | | 6(3s+4)=96 | | (2x+3(x-7))=0 |